Educational Painter for Preschool Children - Ali, Qusay Abboodi (2012)
A lot of people are trying to educate their children via ICT from the early stages of their age. Thus, the learning by drawing using computers is important to promote children skills because drawing develops children imagination. There are a lot of educational programs about the education of children on the drawing, but these programs are designed at a high level in which it is difficult for children to use it. The proposed painter application is designed to teach children drawing, by providing relevant drawing tools. It is also equipped with alphabet learning and it is pronunciation, so that can learn letters while drawing.